A summarization of the visual depression databases for depression detection - Ashraf, Arselan; Gunawan, Teddy Surya; Abdul Rahman, Farah Diyana; Kartiwi, Mira; Ismail, Nanang; Ulfiah, Ulfiah (IEEE, 2020)
Depression is a serious, pervasive mental issue in our general public. A large portion of the populace experiences this issue. Thus there is an outrageous requirement for the depression detection models, which will offer a helpful framework and early identification of depression. There is an essential need for relevant data to set up a depression detection model. This paper presents a brief summarization regarding ten depression datasets available, which will guide the researchers to select an appropriate dataset for their depression detection models. This summarization has been done over the non-verbal signs of depression, data collection techniques, clinical definition, and annotations. Moreover, a tabular list of datasets is provided for quick and easy look through.